Video-Mediated Extension in Ethiopia Household Survey, 2018 - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
These data are generated for the study conducted to evaluate a public extension program that integrates informational video screening with extension service provision to improve farmers’ knowledge and adoption of improved agricultural technologies and practices. Specifically, the study focuses on a program piloted by the Ethiopian Ministry of Agriculture (MoA), regional bureaus of agriculture, and Digital Green, a social enterprise, in the country’s four most agriculturally important regional states. Data for this study are drawn from a series of surveys conducted among farmers participating in the study. A survey of more than 2,400 randomly selected households assigned to one of the three treatment arms after the year 1 (2017) rollout in early 2018, following the meher season harvest. A subsequent round of household surveys was conducted in early 2019, following the year 2 (2018) rollout of the implementation. This dataset includes data from the survey conducted in 2018. Data were collected using two separate questionnaires from both household heads and spouses. The household head questionnaire covered topics including household characteristics, assets, access to services, technology adoption, knowledge of agricultural practices, experience with video, crop sales, non-farm income, savings, food security, shocks, and plot-level information on land use, production, and inputs. The spouse questionnaire included sections on assets, technology adoption, knowledge of agricultural practices, and experience with video.